Hyperbilirubinemia in Gunn Rats is Associated with Decreased Inflammatory Response in LPS-Mediated Systemic Inflammation - Valaskova, Petra; Dvorak, Ales; Lenicek, Martin; Zizalova, Katerina; Kutinova-Canova, Nikolina; Zelenka, Jaroslav; Cahova, Monika; Vitek, Libor; Muchova, Lucie (International journal of molecular sciences, 2019)
Decreased inflammatory status has been reported in subjects with mild unconjugated hyperbilirubinemia. However, mechanisms of the anti-inflammatory actions of bilirubin (BR) are not fully understood. The aim of this study is to assess the role of BR in systemic inflammation using hyperbilirubinemic Gunn rats as well as their normobilirubinemic littermates and further in primary hepatocytes. The rats were treated with lipopolysaccharide (LPS, 6 mg/kg intraperitoneally) for 12 h, their blood and liver were collected for analyses of inflammatory and hepatic injury markers. Primary hepatocytes were treated with BR and TNF-α. LPS-treated Gunn rats had a significantly decreased inflammatory response, as evidenced by the anti-inflammatory profile of white blood cell subsets, and lower hepatic and systemic expressions of IL-6, TNF-α, IL-1β, and IL-10. Hepatic mRNA expression of LPS-binding protein was upregulated in Gunn rats before and after LPS treatment. In addition, liver injury markers were lower in Gunn rats as compared to in LPS-treated controls. The exposure of primary hepatocytes to TNF-α with BR led to a milder decrease in phosphorylation of the NF-κB p65 subunit compared to in cells without BR. In conclusion, hyperbilirubinemia in Gunn rats is associated with an attenuated systemic inflammatory response and decreased liver damage upon exposure to LPS.
Keywords: hepatocyty; RNA, Messenger; hyperbilirubinemie; biologické markery; Lipopolysaccharides; Inflammation; Biomarkers; LPS; lipopolysacharidy; fosforylace; NF-κB; cytokiny; signální transdukce; Phosphorylation; Bilirubin; cytoprotekce; bilirubin; Cytoprotection; Signal Transduction; Hyperbilirubinemia; zánět; Hepatocytes; leukocyty; hyperbilirubinemia; kultivované buňky; Animals; ženské pohlaví; játra; potkani Gunn; zvířata; NF-kappa B; Leukocytes; inflammation; apoptóza; Cells, Cultured; Cytokines; Rats, Gunn; Liver; Female; Gunn rats; messenger RNA; Apoptosis